(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work we propose the identification of the T sign of the Vasconic coin legends uTanbaate and oTtikez with a dental affricate, so that uTanbaate could correspond to *Utzama Ate, i.e., the Celtiberian city name Uxama adapted to the Basque phonetics, followed by a Basque determinant meaning a mountain pass, perhaps the Puerto de Velate, near Ulzama (Navarra). With less certainty, oTtikez could be identified with the nearby village Ostiz. The possible sources of the sign T, the tau gallicum among them, are analysed, together with the possible role of the Etruscan commerce in Languedoc in its adoption.